Open Educational Resources from Vietnamese Students Perceptions in the Foreign Language Learning Classroom - Chanh, Nguyen Huu (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study explores students' perceptions of Open Educational Resources (OER) and their impact on cognitive and affective learning. Based on the Rowells (2015) framework, the research, employed by a mixed-methods approach, combined questionnaire data and semi-structured interviews from a group of students enrolled in an ESP course utilizing OER. A total of 320 undergraduate students voluntarily participated in the study via convenience sampling. Results indicate that students generally had a positive emotional response to OER, appreciating their accessibility, flexibility, and alignment with course objectives. OER were perceived as enhancing learning outcomes, particularly in terms of understanding course materials and fostering critical thinking. However, while students favored OER over traditional textbooks in many aspects, some still found textbooks valuable for certain topics. Additionally, the ability to independently summarize and organize the material was identified as an area where students faced challenges. The study highlights the potential of OER in enhancing educational experiences while emphasizing the need for continuous improvements in content depth and engagement to maximize their effectiveness. It is hoped that OER can play a key role in shaping the future of education by making learning more inclusive and adaptable to diverse learner needs.